The spread of folk medicine in conflict-affected communities, Salah al-Din Governorate as a model: An anthropological field study - Muhammad, Saleh Shabib (Al-Adab Journal, 2022)
The study aimed to identify the spread of folk medicine in conflict-affected communities, Salah al-Din governorate as a model, and to identify the extent of the impact of the economic level on the spread of folk medicine in conflict-affected communities, Salah al-Din governorate as a model, and to identify the effect of education on the spread of folk medicine in conflict-affected communities, Salah al-Din governorate as a model. And to identify the effect of age on the spread of folk medicine in conflict-affected communities, Salah al-Din governorate as a model. The study sample was 241 randomly selected, and the researcher used the descriptive approach. The study came to the following results: 1- The study sample agreed that there is an impact of the economic level on the interaction of individuals in the community With traditional medicine according to societal conditions, especially the conflict, such as Salah al-Din governorate, 2- I find that there is an impact on education in the percentages of using traditional medicine, especially in the case of foreign education, and that folk medicine is widespread among individuals in Salah al-Din governorate, 3- The study sample agreed on the existence of the faith of the largest individuals Life in folk medicine. The researcher made many recommendations.